2022
DOI: 10.7150/ijms.70984
|View full text |Cite
|
Sign up to set email alerts
|

1,25OH-Vitamin D3 and IL-17 Inhibition Modulate Pro-Fibrotic Cytokines Production in Peripheral Blood Mononuclear Cells of Patients with Systemic Sclerosis

Abstract: Objectives: IL-17 modulates the synthesis of several molecules involved in the pathogenesis of Systemic Sclerosis (SSc). Vitamin D (1,25(OH)2D3) shows anti-fibrotic properties and it is able to affect the IL-17 production in several experimental conditions. The aim of this study is to assess the production of IL-17A and pro-fibrotic cytokines in peripheral blood mononuclear cells (PBMCs) from subjects with SSc in basal conditions and after treatment with 1,25(OH)2D3 and IL-17A neutralizing antibodies. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Our results are also in line with preclinical studies demonstrating a downregulation of proinflammatory cytokines production following treatment with vitamin D [30][31][32]. Corrado et al recently demonstrated that 25OHD supplementation was associated with a significant reduction of IL-17A and pro-fibrotic cytokines (FGF2, TGFβ, CTGF) both in patients with systemic sclerosis and in healthy subjects, with a dose-dependent effect [33]. On the other hand, clinical data showed inconsistent results on serum IL-17 and Th-17 cells in subjects with neurologic conditions [8][9][10].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are also in line with preclinical studies demonstrating a downregulation of proinflammatory cytokines production following treatment with vitamin D [30][31][32]. Corrado et al recently demonstrated that 25OHD supplementation was associated with a significant reduction of IL-17A and pro-fibrotic cytokines (FGF2, TGFβ, CTGF) both in patients with systemic sclerosis and in healthy subjects, with a dose-dependent effect [33]. On the other hand, clinical data showed inconsistent results on serum IL-17 and Th-17 cells in subjects with neurologic conditions [8][9][10].…”
Section: Discussionsupporting
confidence: 91%
“…Clinical studies have provided evidence that vit D has the ability to inhibit both IL-17A and pro-fibrotic cytokines, indicating its potential anti-fibrotic effect [25]. These findings support the hypothesis that vit D supplementation in SSc patients may have a potentially beneficial effect on fibrotic processes by inhibiting the production of these cytokines.…”
Section: Discussionsupporting
confidence: 64%
“…In animal SSc models, various cytokines, chemokines, lymphocytes, and monocytes show elevated expression levels. In cellular experiments related to SSc, the imbalance of different cells and cytokines directly affects fibrosis, either promoting or inhibiting it [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%